Intraoperative conversion of coronary bypass grafting from cardio-pulmonary bypass to off-pump procedure forced by antithrombin III deficiency – a case report - Banyś, Andrzej; Jander, Sławomir; Grychowska, Justyna; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The essential condition of safe application of cardio-pulmonary bypass (CPB) is to obtain a proper level of heparinization in the operated patient, measured by activated clotting time (ACT). The present paper is a case report of forced intraoperative change of technique of surgical myocardial revascularization in a 78-year-old woman caused by antithrombin III deficiency.